The impact of an educational program based on the meta-Cognitive strategies in the development of systemic intelligence among the students of the Ninawa Technical Institute - Hamid Al-Dulami, Yasir Mahfoodh; Hamdullah Al Fahadee, Ammar Talal (Opción, 2019)
The aim of the study was to identify the impact of an educational program based on the meta-knowledge strategies in the development of organizatio- nal intelligence in the students of the Ninawa Technical Institute in the light of the variables of the group and sex and the interaction between them. The sample consisted of 64 students from the accounting and financial and banking techniques, (32) students from the accounting department. The control group consisted of (32) students from the Department of Finance and Banking, as well as equivalence procedures in the variables (tribal test, age in months, gender). The researcher devised an educational program based on meta-knowledge strategies with (14) sessions based on the four meta-knowledge skills according to the For Sternberg’s theory (awareness- planning- control- Evaluation), The results showed that there was a statisti- cally significant difference among the research groups between the averages of the development of systemic intelligence and the benefit of the experi- mental group. There was a statistically significant difference among the research groups between the averages of developing systemic intelligence and gender and interaction Between group and gender in the development of systemic intelligence and for the benefit of females.